Performance evaluation for SE113 flow control system plant using self-tuning fuzzy PI controller: article / Ahmad Shahir Mustaffa - Mustaffa, Ahmad Shahir (2016)
The aim of this project is to evaluate the process performance of SE113 Flow Control System Plant using self-tuning Fuzzy PI controller. The experimental data is used to model the process and the control analysis is done using Matlab Simulink. The performance evaluation is based on the percent overshoot, rise time and settling time of the process. The overall performance is compared with the conventional Proportional-Integral control method. The results had shown that self-tuning Fuzzy PI controller simplify the tediousness in tuning the controller and enhance the capability of PI controller-only.